The Hepatoprotective and Hepatotoxic Roles of Sex and Sex-Related Hormones - Xu, Linlin; Yuan, Yuan; Che, Zhaodi; Tan, Xiaozhi; Wu, Bin; Wang, Cunchuan; Xu, Chengfang; Xiao, Jia (Frontiers in Immunology, 2022)
Most liver diseases, including acute liver injury, drug-induced liver injury, viral hepatitis, metabolic liver diseases, and end-stage liver diseases, are strongly linked with hormonal influences. Thus, delineating the clinical manifestation and underlying mechanisms of the “sexual dimorphism” is critical for providing hints for the prevention, management, and treatment of those diseases. Whether the sex hormones (androgen, estrogen, and progesterone) and sex-related hormones (gonadotrophin-releasing hormone, luteinizing hormone, follicle-stimulating hormone, and prolactin) play protective or toxic roles in the liver depends on the biological sex, disease stage, precipitating factor, and even the psychiatric status. Lifestyle factors, such as obesity, alcohol drinking, and smoking, also drastically affect the involving mechanisms of those hormones in liver diseases. Hormones deliver their hepatic regulatory signals primarily via classical and non-classical receptors in different liver cell types. Exogenous sex/sex-related hormone therapy may serve as a novel strategy for metabolic liver disease, cirrhosis, and liver cancer. However, the undesired hormone-induced liver injury should be carefully studied in pre-clinical models and monitored in clinical applications. This issue is particularly important for menopause females with hormone replacement therapy (HRT) and transgender populations who want to receive gender-affirming hormone therapy (GAHT). In conclusion, basic and clinical studies are warranted to depict the detailed hepatoprotective and hepatotoxic mechanisms of sex/sex-related hormones in liver disease. Prolactin holds a promising perspective in treating metabolic and advanced liver diseases.